Nanoparticles and plants: A focus on analytical characterization techniques - Pinheiro, Sergimar Kennedy de Paiva; Pontes, Montcharles da Silva; Miguel, Thaiz Batista Azevedo Rangel; Grillo, Renato [UNESP]; Souza Filho, Antonio Gomes de; Miguel, Emilio de Castro (Elsevier, 2024)
Nanotechnology has brought about significant progress through the use of goods based on nanomaterials. However, concerns remain about the accumulation of these materials in the environment and their potential toxicity to living organisms. Plants have the ability to take in nanomaterials (NMs), which can cause changes in their physiology and morphology. On the other hand, nanoparticles (NPs) have been used to increase plant development and control pests in agriculture by including them into agrochemicals. The challenges of the interaction, internalization, and accumulation of NMs within plant tissues are enormous, mainly because of the various characteristics of NMs and the absence of reliable analytical tools. As our knowledge of the interactions between NMs and plant cells expands, we are able to create novel NMs that are tailored, targeted, and designed to be safe, thus minimizing the environmental consequences of nanomaterials. This review provides a thorough examination and comparison of the main microscopy techniques, spectroscopic methods, and far-field super-resolution methodologies used to examine nanomaterials within the cell walls of plants.
Keywords: Electron microscopy; High-resolution microscopy; Nanomaterials; Nanoparticle mapping; Plant tissue